Agricultural Knowledge Networks in Northern Ghana - Bellwood-Howard, Imogen; Alidu, Abdul-Fatahi (The International Journal of Sociology of Agriculture and Food, 2018)
Farmers, researchers and extension officers in Northern Ghana encounter productivity problems, such as striga, acidity, hardpan and bochaa (a Dagbani word denoting low productivity). We undertook a mainly qualitative study using interviews, focus groups and a workshop to investigate, from a science and technology studies perspective, the intersections between their different ways of understanding these problems. Different actors construct definitions of what productivity problems are during the performance of their occupations, for example through peer association and application of available solutions. Actors with different occupations thus disagree over what productivity problems are, with farmers defining them by their symptoms and researchers by the physical, biological and chemical mechanisms through which they act. Extension services have not trained officers to reconcile these identity-linked understandings, which has hitherto prevented hybrid knowledge about such problems from emerging. Yet actors agree on the utility of certain management practices, such as manuring. These have the potential to act as boundary objects, pointing to the possibility of a composite knowledge network within which different actors retain their occupational identities and discrete knowledges, yet share common solutions. Extension agents and researchers would benefit from training on the use of boundary objects as communication tools.